PENERAPAN DIVERSI TERHADAP ANAK DALAM SISTEM HUKUM PIDANA INDONESIA - Fransiska Novita Eleanora (Fakultas Hukum Universitas Kristen Indonesia, 2016)
Diversion is a transfer of settlement of cases of children who are suspected of certain crimes from the formal criminal to a peaceful settlement between the suspect / accused / offender with the victim facilitated by family and / or community, Supervisor of Community Kids, Police, prosecutor or judge, Therefore, not all cases of children in conflict with the law must be resolved through the formal justice, and provide an alternative to the settlement with the restorative justice approach then, on cases of children in conflict with the law to do the diversion of the best interest of the child and taking into account the justice victim. While the Indonesian criminal code, known retaliation, which according to his ways, by providing appropriate sanctions to perpetrators, the purpose of this paper to know whether the Indonesian criminal law regulating the diversion of the dispute settlement children, method of writing is a literature study, the result is a process of diversion is regulated by a special regulation children’s Act, and is promoting the rights of children.Kata kunci: diversi, anak, hukum pidana